A qualitative interview study: patient accounts of medication use in early rheumatoid arthritis from symptom onset to early postdiagnosis. Issue 2 (13th February 2013) - Townsend, Anne; Backman, Catherine L; Adam, Paul; Li, Linda C
Abstract : Objective: To examine accounts of medication use in participants with early rheumatoid arthritis (RA) from symptom onset to early postdiagnosis. Design: Qualitative study with in-depth, personal interviews. Participants: 37 women and one man, aged 30–70s, with a diagnosis of RA <12 months. Main outcome measure: Participants' experiences and feelings of medication use in early RA. Setting: British Columbia, Canada. Results: Medications were central to how people managed symptoms and disease. Two main themes were identified, showing that optimum medication use was hampered, and how this related to delayed diagnosis and effective care. The first theme, 'paradox of prediagnosis reliance on over the counter (OTC) medications', describes how people's self-management with OTC medications was 'effective'. Participants relied extensively on OTC medications for pain relief and to maintain 'normal life'. However, as this contributed to delayed medical consultation, diagnosis and effective treatment, OTC medication was also potentially detrimental to disease outcome. The second theme, 'ambivalence around prescription medications post diagnosis', describes how adherence was hindered by patient beliefs, priorities and ambivalence towards medications. Conclusions: This study highlights how people use medications in early RA and contributes to a better understanding of medication use that may transfer to other conditions. Given the drive towards active self-management in healthcare and patients' ambivalence about using strong medications, an in-depth understanding of how these combined factors impact patient experiences will help healthcare providers to support effective medication practices. The reported extensive reliance on OTC medications may speak to a care gap needing further investigation in the context of health behaviours and outcomes of patient self-management.